Analisa Sambungan Pengelasan Gas Metal Arc Welding (GMAW) menggunakan pengujian metalografi Di PT. XYZ - Irpan Kurniawan; Ratna Dewi Anjani; Rizal Hanifi (Jurnal Ilmiah Wahana Pendidikan, 2022)
Welding is an important factor in the industrial world because welding is used in all aspects such as joining, repairing or repairing materials. In various aspects of welding, failures often occur, either broken, or defects that cannot be seen by the naked eye. Therefore, testing in welding joints becomes necessary to see whether the welding can be said to be good or bad. Various welding tests that are familiar are microstructural testing and macrostructural testing. These two tests have different roles or functions, for microstructural testing it is useful to see the density of a weld, to determine the type of phase formed in a welding, to determine grain boundaries, and so on. Meanwhile, for macrographic testing, the function is to find out into a welding, find out the defects that occur in the welding and so on. For more clarity the author will discuss metallographic testing in a welding.